The Fate of Meniscus Tears Left in situ at the time of Anterior Cruciate Ligament Reconstruction: A 6-year Follow-up Study from the MOON Cohort - Duchman, Kyle R. (Am J Sports Med, 2015)
BACKGROUND: The management of meniscus tears identified at the time of primary ACL reconstruction is highly variable and includes repair, meniscectomy, and non-treatment. HYPOTHESIS/PURPOSE: The purpose of this study is to determine the reoperation rate for meniscus tears left untreated at the time of ACL reconstruction with minimum follow-up of 6 years. We hypothesize that small, peripheral tears identified at the time of ACL reconstruction managed with “no treatment” will have successful clinical outcomes. STUDY DESIGN: Retrospective study of a prospective cohort; Level of Evidence, 3 METHODS: Patients with meniscus tears left untreated at the time of primary ACL reconstruction were identified from a multicenter study group with minimum 6-year follow-up. Patient, tear, and reoperation data were obtained for analysis. Need for reoperation was used as the primary endpoint, with analysis performed to determine patient and tear characteristics associated with reoperation. RESULTS: There were 194 patients with 208 meniscus tears (71 medial; 137 lateral) left in situ without treatment with complete follow-up for analysis. Of these, 97.8% of lateral and 94.4% of medial untreated tears required no reoperation. Sixteen tears (7.7%) left in situ without treatment underwent subsequent reoperation: 9 tears (4.3%) underwent reoperation in the setting of revision ACL reconstruction and 7 tears (3.4%) underwent reoperation for isolated meniscus pathology. Patient age was significantly lower in patients requiring reoperation, while tears measuring ≥ 10 mm more frequently required reoperation. CONCLUSIONS: Lateral and medial meniscus tears left in situ at the time of ACL reconstruction did not require reoperation at minimum 6-year follow-up for 97.8% and 94.4% of tears, respectively. These findings reemphasize the low reoperation rate following non-treatment of small, peripheral lateral meniscus tears while noting less predictable results for medial meniscus tears left without treatment.